Scientific Misconduct in Asbestos-related Occupational Health Studies: A Literature Review on the Impact of Intellectual Dishonesty to Scientific Research : A Literature Review on the Impact of Intellectual Dishonesty to Scientific Research - Dyah Ayu Pradnyaparamitha; Hirzi Salsabil Zulkarnain; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2023)
Introduction: The asbestos industry actively tries to delay adequate asbestos protection regulation in workplaces by systematic manipulation and scientific misconduct. This research aims to compile several of their efforts throughout the years to study their efforts and prevent them. Methods: A literature review was conducted to explore instances of scientific misconduct in occupational health studies related to asbestos in November 2022. The sources were taken from Google Scholar and PubMed. From the entire search, 6 relevant studies were reviewed. Results: Throughout the world, the asbestos industry has been responsible for delays in adequate asbestos regulations. Several systematic scientific misconduct regarding asbestos use happened in 1930s United States, as well as fraudulent research regarding asbestos in early 2000s Brasil. Scientific misconducts can directly influence the direction of occupational health research involving asbestos exposure, resulting in delays in adequate regulation implementation.Conclusions: The dangers of asbestos to workers exposed is already firmly established. The asbestos industry has been deliberately manipulating scientific data to sway corporate and public views to prolong the viability of asbestos production and daily use. They achieved this using industry-backed scientific discourse, direct manipulation of research data, as well as direct manipulation of research data publication.